THE EVOLUTION OF REAL DIFFICULTY VALUE OF UNEVEN BARS ROUTINES FROM ELITE GYMNASTS IN LAST 5 OLYMPIC CYCLES - José Ferreirinha; Joana Carvalho; Cristina Côrte-Real; António Silva (Science of Gymnastics Journal)
Purpose of the present study was to characterize and analyse the evolution of real difficulty value of full routines, parts and specific kind of elements of Uneven Bars. Besides the full routine difficulty were analyzed the mount, dismount, flight elements, first and second half routines, bars changes, elements executed on low and high bar, number of elements of value D and higher, “in bar elements” and special connections. In total, 104 routines from world championships and Olympic Games finals of uneven bars were analysed between 1989 and 2008. As main results was observed significant increases in all studied variables. Real difficulty value of complete routines ranged from 3.15 to 5.80 points between first and last Olympic cycles analyzed. Special evolution of difficulty values was observed in number of elements D, E and F (from 2.80 to 8.05), total number of bonus connections (from 0.40 to 4.19) and in “in bar” elements (0.25 to 1.57). Based on results we may conclude that uneven bars routines suffered a significant evolution in difficulty and, in some specific kind of elements, just with last changes in Code of Points was possible to confirm the announced increases in quantity and difficulty such as the flight elements.